INVESTIGATION OF STUDENTS’ PERCEPTION TOWARD E-LEARNING IN THE FIFTH SEMESTER OF ENGLISH LANGUAGE EDUCATION UNDIKSHA - ., Putu Nopa; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Universitas Pendidikan Ganesha, 2017)
Penelitian ini bertujuan untuk menyelidiki persepsi siswa tentang e-learning. Penelitian ini dilakukan untuk mengetahui persepsi mahasiswa terhadap pemanfaatan teknologi informasi terutama e-learning dalam pembelajaran di kelas. Data penelitian dikumpulkan di Program Studi Bahasa Inggris UNDIKSHA dengan 80 kuesioner. Hasil penelitian menunjukkan bahwa mayoritas siswa berpendapat bahwa e-learning adalah ide inovatif dan harus didorong. Dan pembelajaran hybrid, yang merupakan kombinasi dari pembelajaran online dan pembelajaran tatap muka, adalah cara belajar yang disukai responden. Kata Kunci : E-learning, Model penerimaan teknologi (TAM), pembelajaran berbasis web, pembelajaran hybrid, pembelajaran sepenuhnya online. This study aims to investigate students' perceptions of e-learning. This research was conducted to determine students' perceptions in the use of information technology, especially e-learning in classroom learning. The research data were collected at English Language Education of UNDIKSHA with 80 questionnaires. The outcomes of the study showed the majority of the students think e-learning is an innovative idea and must be encouraged. Hybrid learning, which is a combination of online learning and face-to-face learning, is the preferred mode of learning for the respondents. keyword : E-learning, Technology Acceptance Model (TAM), Web-assisted learning, Hybrid learning, Fully-online learning.